Application Of Artificial Intelligence In Improving The Efficiency Of Corporate Information Systems - Adi Ahmad (Journal Informatic, Education and Management (JIEM), 2023)
Artificial Intelligence (AI) has been widely applied in various fields, including important aspects in the development of enterprise information systems. This research aims to explore the use of AI in improving the efficiency of enterprise information systems and analyse its impact on organisational performance. In this research method, we collected primary data from several companies that have implemented AI systems in their operations. Secondary data was also collected from related literature, including case studies and previous research in this field. Furthermore, we conducted a qualitative analysis of the data and a quantitative evaluation of the impact of AI implementation in improving the efficiency of information systems. The results show that the implementation of AI has resulted in a significant increase in the efficiency of the company's information system. AI-assisted systems are able to automatically process and analyse data, predict market trends, identify anomalies, and provide strategic recommendations for decision-making. These efficiencies in turn improve operational performance, lower costs, and enhance more timely and accurate decision-making. We conclude that the use of AI in enterprise information systems effectively improves operational efficiency and organisational performance. However, important steps need to be taken to ensure successful implementation of AI, such as providing adequate resources, developing employee competencies, and considering the social and ethical impacts of using AI in a business context.